2019
DOI: 10.3892/etm.2019.8345
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical value of lncRNA MALAT1 and lncRNA ANRIL in glaucoma patients

Abstract: Expression and clinical value of long non-coding RNA (lncRNA) MALAT1 and lncRNA ANRIL in glaucoma patients were investigated. Altogether 86 glaucoma patients who were diagnosed (study group) and 86 people who underwent physical examinations and were confirmed to be healthy (control group) in the Hospital of Chengdu University of Traditional Chinese Medicine from January 2016 to June 2018 were enrolled. Expression of the serum lncRNA MALAT1, lncRNA ANRIL, pigment epithelium-derived factor (PEDF), homocysteine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“… 29 As a sulfur-containing amino acid, a connection between lncRNAs and inflammatory can be established through Hcy, because it can induce oxidative stress and mediate inflammation in many cell types. 30 , 31 In addition, evidence also indicated that alteration of lncRNA-H19 promoter methylation through TNF-α/NF-κB pathway was associated with Hcy-induced oxidative stress. 32 , 33 , 34 A previous study demonstrated that LOC646329-variant D exerted its suppression effect on colorectal cancer progression via regulating Wnt and TGFB signaling pathways, which characterized LOC646329 as a novel potential therapy target.…”
Section: Discussionmentioning
confidence: 99%
“… 29 As a sulfur-containing amino acid, a connection between lncRNAs and inflammatory can be established through Hcy, because it can induce oxidative stress and mediate inflammation in many cell types. 30 , 31 In addition, evidence also indicated that alteration of lncRNA-H19 promoter methylation through TNF-α/NF-κB pathway was associated with Hcy-induced oxidative stress. 32 , 33 , 34 A previous study demonstrated that LOC646329-variant D exerted its suppression effect on colorectal cancer progression via regulating Wnt and TGFB signaling pathways, which characterized LOC646329 as a novel potential therapy target.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the increased expression of lncRNA MALAT1 and lncRNA ANRIL detected in the serum of glaucoma patients correlated with the pathological classifications of the patients. Statistical analysis of the data showed that the diagnostic specificity and sensitivity of the combined detection of both RNA molecules were higher than those of either of the two molecules alone (Zheng et al, 2020 ).…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Previous studies have shown that lncRNAs are associated with diverse ocular diseases, including diabetic retinopathy, retinal neovascularization, glaucoma ( Zheng M. et al, 2020 ), cataracts ( Tu et al, 2020 ), proliferative vitreoretinopathy ( Ni et al, 2021 ) and retinoblastoma ( Wang H. et al, 2021 ). RNA sequencing (RNA-seq) of a guinea pig form-deprived myopia (FDM) model and a lens-induced myopia (LIM) model has also suggested that there is differential lncRNA expression in the ocular posterior pole ( Geng et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%